First discoveries of z > 6 quasars with the DECam Legacy Survey and UKIRT hemisphere survey - Wang, Feige; Fan, Xiaohui; Yang, Jinyi; Wu, Xue-Bing; Yang, Qian; Bian, Fuyan; McGreer, Ian D.; Li, Jiang-Tao; Li, Zefeng; Ding, Jiani; Dey, Arjun; Dye, S.; et al. (IOP Publishing, 2017)
We present the first discoveries from a survey of z 6 quasars using imaging data from the DECam Legacy Survey (DECaLS) in the optical, the UKIRT Deep Infrared Sky Survey (UKIDSS) and a preliminary version of the UKIRT Hemisphere Survey (UHS) in the near-IR, and ALLWISE in the mid-IR. DECaLS will image 9000 deg2 of sky down to z AB ~ 23.0, and UKIDSS and UHS will map the northern sky at 0 < decl. < +60°, reaching J VEGA ~ 19.6 (5-σ). The combination of these data sets allows us to discover quasars at redshift z 7 and to conduct a complete census of the faint quasar population at z 6. In this paper, we report on the selection method of our search, and on the initial discoveries of two new, faint z 6 quasars and one new z = 6.63 quasar in our pilot spectroscopic observations. The two new z ~ 6 quasars are at z = 6.07 and z = 6.17 with absolute magnitudes at rest-frame wavelength 1450 Å being M 1450 = −25.83 and M 1450 = −25.76, respectively. These discoveries suggest that we can find quasars close to or fainter than the break magnitude of the Quasar Luminosity Function (QLF) at z 6. The new z = 6.63 quasar has an absolute magnitude of M 1450 = −25.95. This demonstrates the potential of using the combined DECaLS and UKIDSS/UHS data sets to find z 7 quasars. Extrapolating from previous QLF measurements, we predict that these combined data sets will yield ~200 z ~ 6 quasars to z AB < 21.5, ~1000 z ~ 6 quasars to z AB < 23, and ~30 quasars at z > 6.5 to J VEGA < 19.5.